Impact of COVID-19 on routine childhood immunisations in low- and middle-income countries: A scoping review. - Milena Dalton; Benjamin Sanderson; Leanne J Robinson; Caroline S E Homer; William Pomat; Margie Danchin; Stefanie Vaccher (Public Library of Science (PLoS), 2023)
Routine vaccines are critical to child health. The COVID-19 pandemic significantly impacted essential health services, particularly in low-and middle-income countries (LMICs). We reviewed literature to determine the impact of COVID-19 on service delivery and uptake of routine childhood immunisation in LMICs. We reviewed papers published between March 2020 and June 2022 using a scoping review framework, and assessed each paper across the World Health Organisation health system strengthening framework. Our search identified 3,471 publications; 58 studies were included. One-quarter of studies showed routine childhood immunisation coverage declined (10% to 38%) between 2019 to 2021. Declines in the number of vaccine doses administered (25% to 51%), timeliness (6.2% to 34%), and the availability of fixed and outreach services were also reported. Strategies proposed to improve coverage included catch-up activities, strengthening supply chain and outreach services. Re-focusing efforts on increasing coverage is critical to improve child health and reduce the likelihood of disease outbreaks.